The Relationship Between Osteoporotic Risk Factors and Bone Mineral Density - Şule Şahin Onat; Sibel Ünsal Delialioğlu; Sumru Özel (Galenos Yayinevi, 2013)
Objective: Since osteoporosis is a preventable disease to some extent, risk factor determination and if possible modification is very important. The aim of this study is to identify the relationship between ostoporotic risk factors and bone mineral density results and emphasize the importance of risk factors. Materials and Methods: The study comprised 103 postmenopausal osteoporotic women. Demographic characteristics, osteoporortic risk factors, lumbar vertebrae and femur neck T scores were recorded. Relationships between lumbar vertebra and femur neck T scores and risk factors were statistically studied. Results: Advanced age, low physical activity status, inadequte dietary calcium intake and vertebral compression fractures were found to be associated with low bone mineral density results in postmenopausal osteoporotic women whereas marital status, occupation, education level and familial fracture history were not. Furthermore early menopause was found to be associated with low femoral T scores and smoking with low lumbar T scores. Tendency to fall and number of chronic diseases were irrelevant to bone mineral density. Conclusions: Risk factor assesment is still important for osteoporosis prevention. (Turkish Journal of Osteoporosis 2013;19:74-80)